Culture of Rajasthan and its inherent folk music: राजस्थान की संस्कृति व उनमें निहित लोकसंगीत - Chaturvedi, Saraswati (International Journal of Research -GRANTHAALAYAH, 2018)
The state of Rajasthan, as the name suggests, is a state filled with many colors, the food, dress and dress of this state are very much embedded in the folk culture, folklore, folklore, folk dance and folklore. Word meaning The word 'Lok' is a very ancient word, the meaning of the word 'Lok' can be derived from the mass society which is deeply spread on the earth. The word 'Lok' refers to an important mass community. Folk songs used in Rajasthan's folk culture In these folk songs we have the philosophy of folk culture of Rajasthan, they can be categorized as follows - Ritual folk songs: Wadhwa, Chalk, India, Zartzga, turmeric, horse etc. are the main folk songs related to the rites. Folklore related to dance: Different types of folk songs are sung by different castes in dances performed on festivals. Folklore of commercial castes: In Rajasthan, many castes sing these folk songs to make a living. Folklore of Bhil caste: The life of Bhil caste people is full of dance, songs and humor humor. The following institutions are contributing immensely in promoting the folk culture of Rajasthan. Their names are Jawahar Arts Center Jaipur, Western Zone Cultural Center Udaipur etc. In this way we can say in the context of folk music of Rajasthan that their future will be bright. राजस्थान राज्य जैसा कि नाम से ही प्रतीत होता है कि यह राज्य कई रंगों से भरा हुआ राज्य हैं, इस प्रदेश का खान-पान, पहनावा यहाँ की लोकसंस्कृति, लोकवाद्य, लोकगीत, लोकनृत्य तथा लोकनाट्य जनसमुदाय में अत्यन्त रूप से समाहित दिखाई देते है। लोक शब्द से तात्पर्य ’लोक’ शब्द एक बहुत प्राचीन शब्द है ’लोक’ शब्द का अर्थ उस जन समाज से लगाया जा सकता है जो गहराई से पृथ्वी पर फैला रहता है। ’लोक’ शब्द एक महत्वपूर्ण जन समुदाय की ओर संकेत करता है। राजस्थान की लोकसंस्कृति में प्रयुक्त लोकगीत इन लोकगीतों में हमें राजस्थान की लोक संस्कृति के दर्शन होते हैं उनका निम्नलिखित प्रकार से वर्गीकरण किया जा सकता है - संस्कार सम्बन्धी लोकगीतः- वाधावा, चाक, भारत, जरतजगा, हल्दी, घोड़ी आदि संस्कार सम्बन्धी प्रमुख लोकगीत होते हैं। नृत्य सम्बन्धी लोकगीतः- त्यौहार-पर्वों पर किये जाने वाले नृत्यों में विभिन्न जातियों द्वारा विभिन्न प्रकार के लोकगीत गाये जाते हैं। व्यवसायिक जातियों का लोकगीतः- राजस्थान में अनेक जातियाँ अपनी जीविका चलाने के लिये इन लोकगीतों को गाती है। भील जाति के लोकगीतः- भील जाति के लोगों का जीवन नृत्य, गीतों एवं हास्य विनोद से परिपूर्ण होता हैं। राजस्थान की लोक संस्कृति को प्रोत्साहन देने में निम्नलिखित संस्थाऐं अत्यधिक योगदान दे रही हैं। उनके नाम है, जवाहर कला केन्द्र जयपुर, पश्चिम क्षेत्र सांस्कृतिक केन्द्र उदयपुर आदि। इस प्रकार से हम राजस्थान के लोक संगीत के सन्दर्भ में कह सकते हंै कि इनका भविष्य उज्जवल रहेगा।